Enhanced microwave absorption property of epoxy nanocomposites based on PANI@Fe3O4@CNFs nanoparticles with three-phase heterostructure. (9th February 2018) - Yang, Lingfeng; Cai, Haopeng; Zhang, Bin; Huo, Siqi; Chen, Xi
Abstract: Novel electromagnetic functionalized carbon nanofibers (CNFs) have been synthesized by coating with Fe3 O4 magnetite nanoparticles and conducting polymers polyaniline (PANI) on CNFs through a layer by layer assembly. The Fe3 O4 @CNFs were first prepared by coating nano-Fe3 O4 particles on CNFs via co-precipitation method; Then the PANI was coated on Fe3 O4 @CNFs using an in situ polymerization process to obtain PANI@Fe3 O4 @CNFs nanoparticles. The prepared PANI@Fe3 O4 @CNFs nanoparticles were dispersed in the epoxy matrix to fabricate microwave absorbing nanocomposites. Compared with the Fe3 O4 @CNFs/epoxy nanocomposites, the PANI@Fe3 O4 @CNFs/epoxy nanocomposites exhibit better microwave absorbing properties. The composite containing 15 wt% of PANI@Fe3 O4 @CNFs with the thickness of 2 mm showed a minimum reflection loss (RL) value of −23.7 dB with an effective absorption bandwidth which is about 3.7 GHz (11.9–15.6 GHz) in the frequency range of 1–18 GHz, indicating that it is an attractive candidate for efficient microwave absorber. A potential absorption mechanism was proposed for enhancement of the impedance-matching condition and electromagnetic wave-attenuation characteristic of materials. Specifically, the impedance-matching condition was improved by the combination of conductive polymers and magnetic nanoparticles with CNFs. The electromagnetic wave attenuation characteristic was enhanced by multiple reflections, due to the increased propagation paths.